Optimizing Prisoner Care Services by Enhancing Police Performance in Indonesian National Police Detention Centers - Tua, Rolando; Rizali, Deden Fajar; Jamaludin, Ahmad (LifeSciFi, 2025)
The National Police is a state apparatus responsible for maintaining public security and order, enforcing the law, and providing protection and services to the community. This study aims to explore the optimization of prisoner care services through efforts to improve the performance of Indonesian National Police members. Employing an empirical juridical approach, the research focuses on the Directorate of Prisoners and Evidence (Direktorat Tahanan dan Barang Bukti/DITTAHTI) Detention Center of the West Java Regional Police. The findings reveal that prisoner care services have been running effectively, despite a shortage of personnel specifically assigned to the care and supervision of detainees. Optimization efforts are reflected in activities such as maintaining detention center facilities, providing food and clothing for detainees, fulfilling their basic needs, maintaining cleanliness, offering physical and spiritual guidance, facilitating visitation services, ensuring access to healthcare, and conducting programs for discipline, legal awareness, and grievance resolution. These service improvements aim to support a humane and accountable investigation process. The performance of Indonesian National Police personnel significantly influences the quality of prisoner care services. As such, well-performing officers contribute to more effective and satisfactory services, directly impacting public trust and satisfaction with the role of the police in managing detainee welfare.